"Is it worth living?" psychosocial challenges of childhood sexual abuse survivors aging with HIV. Issue 3 (4th March 2023) - Hart, Mackenzie J.; Brown, Monique J.; Harrison, Sayward E.; Nkwonta, Chigozie A.; James, Titilayo; Kaur, Amandeep
ABSTRACT: Older adults living with HIV (OALH) undergo challenges such as comorbidities, social isolation, and "double stigma" associated with their HIV and aging statuses. Simultaneously, research has shown that experiences of childhood sexual abuse (CSA) continue to impact the quality of life across the lifespan and may pose unique hardships for older adults. Despite the high prevalence of trauma among people living with HIV, research examining the psychosocial challenges of OALH with a CSA history is scant. To address this gap in the literature, this study aimed to explore psychosocial challenges among OALH who are CSA survivors using a qualitative approach. Twenty-four in-depth, semi-structured interviews were completed with OALH (age 50 years and older) who reported histories of CSA. Multiple coders and an inductive coding process were employed for data analysis. Four main themes regarding psychosocial challenges emerged from the analysis: (1) depression and suicidal ideation, (2) fear and anxiety, (3) social support issues, and (4) memory issues. The authors discuss the implications of these findings and the importance of trauma-informed treatment for these individuals.